2020
DOI: 10.9734/ajaees/2020/v38i930417
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Bangladesh: Socio-Economic Analysis towards the Future Correspondence

Abstract: The COVID-19 has caused gigantic negative effects on populace wellbeing, society, education, and the economy in Bangladesh. The aim is to deliver a comprehensive overview of the observed and the possible impacts that could appear in the coming days. The study is based on secondary information. During the early period, due to a lack of accurate facts about the case affected and death tension up-and-down among the nations. The total number of confirmed cases is increasing following geometric patterns in Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Moreover, additional unexpected costs were, sometimes involuntarily, compensated for by a significant reduction in education expenditure. Note that it is not clear if the reduction in education expenditure was due to costs-savings caused by government-imposed school closures [ 47 ] or if children of school age had to (temporarily) drop out of school to support the household, as other research has found [ 48 ], or both. In either case, the observed reduction in education expenditure is indicative of lower rates of children attending schools.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional unexpected costs were, sometimes involuntarily, compensated for by a significant reduction in education expenditure. Note that it is not clear if the reduction in education expenditure was due to costs-savings caused by government-imposed school closures [ 47 ] or if children of school age had to (temporarily) drop out of school to support the household, as other research has found [ 48 ], or both. In either case, the observed reduction in education expenditure is indicative of lower rates of children attending schools.…”
Section: Discussionmentioning
confidence: 99%
“…Also, milk prices have drastically declined during COVID-19. Moreover, due to COVID, Bangladesh has lost about 67 million US dollars as a result of discarding fresh milk (Begum et al, 2020 ). Nepal has suffered 17 million US dollars in losses in dairy products (Poudel et al, 2020 ).…”
Section: Impact Of Covid-19 On Livestock Production Systemsmentioning
confidence: 99%
“…But, the government may be unable to control circumstances. So, general public participation, political leader and supporters, industrials, business man, pharmaceutical companies, garment owners, medical practitioner and international supports are required on a quick basis to overcome smoothly [38], [41]- [43]. Therefore, we need to take necessary steps for maintaining knowledge and awareness practices for healthy life during lockdown in Bangladeshi community.…”
Section: Maintaining Social Distance By Occupation and Staying At Home By Respondents' Age Groupmentioning
confidence: 99%